PROFIL IST MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS “YY” - Shanty Sudarji; Akira Akira; Michael Yeong; Stefanus Reinhard (Universitas Bunda Mulia, 2012)
Human intelligence is an abstract thing. Intelligence can be measured in many ways, one of which is to use an intelligence test. Intelligenz Structure Test (IST) is a test instrument used in clinical psychology and educational settings to measure one's intelligence capacity. IST was created by Amthauer and has been tested in a variety of research settings. The subjects in the study totaled 71 students consisted of students of 2008 through 2011 are active in the period 2011-2012 semester. This type of research is quantitative descriptive. The results showed that the intelligence capacity of students of “YY” University Psychology is at the level of average intelligence scores (IQ) = 97 (IST scale). The most prominent feature is the ability of catching the essence or meaning or understanding expressed in the language, the language of inductive thinking, the ability to explore the feelings or empathy. Thought patterns and ways of thinking are found to be flexible and verbal theoretical. Keywords: Intelligenz Structure Test (IST), picture profiles based on the IST, Student of Psychological Program